Suicide attempts and clinical severity of eating disorders:An exploratory study - Bárbara C. Machado (Terapia Psicológica, 2004)
The present study examines whether eating disorders patients with suicide attempts present differences in disorderedeating and clinical traits compared to those without suicide attempts. A total of 144 patients with eating disorders (65anorexia nervosa and 79 bulimia nervosa) completed the Eating Disorders Inventory (EDI; Garner, Omstead & Polivy,1983), the Symptom Checklist 90 Revised (SCL-90; Derrogatis, 1977), and a questionnaire to assess eating behaviorsand attitudes, information regarding suicide behaviors and other related traits (PQB and TIB (Machado & Soares, 2000);Cost B6 (Machado & Soares, 2000). Eating disorder patients with suicide attempts differed from there peers regarding tothe weight history, mean of binge-purge attacks, use of vomiting to weight control, use of alcohol and psycho tropics,menstrual pattern, sexual attitude, and in some EDI and SCL-90 subscales. The findings of the current study show thatsuicide attempts are related to some indices of symptom history and severity for both diagnostic groups of eating disorders